AN ANALYSIS OF THE TEKEL RESISTANCE AT TURKEY IN THE CONTEXT OF SOCIAL MOVEMENTS - YÄ±ldÄ±rÄ±m, Yavuz (European Scientific Journal, ESJ, 2013)
This article analyzes the Tekel Resistance during December, 2009-March, 2010 in Ankara-Turkey through social movements theory. This opposition action has a unique meaning across Turkish social struggle because of its distinction in structural and cultural bases. While it had mobilized the workers and their families as an organizational opposition, it turned into a grass-root resistance against government and the union leadership. This study focuses on the collective action of Tekel workers in terms of social movements literature and whether this action has a social movement character. The Tekel resistance as a grass-root movement against both the government and the unioun is discussed in the context of â€œcontentious politicsâ€ and â€œnew social movementsâ€ and the events of the 78-days resistance are matched with the concepts of these two approaches. I would argue that while it as an unusual experiment creates a social movement base and ensures new networks, it is not exactly a social movement according to the two different approaches of social movements.